Evidence for clinical, genetic and biochemical variability in spinal muscular atrophy with progressive myoclonic epilepsy. (21st November 2013) - Dyment, D.A.; Sell, E.; Vanstone, M.R.; Smith, A.C.; Garandeau, D.; Garcia, V.; Carpentier, S.; Le Trionnaire, E.; Sabourdy, F.; Beaulieu, C.L.; Schwartzentruber, J.A.; McMillan, H.J.; et al.
<x xml:space="preserve">Abstract</x> Spinal muscular atrophy with progressive myoclonic epilepsy (SMA‐PME) is a recently delineated, autosomal recessive condition caused by rare mutations in the N‐acylsphingosine amidohydrolase 1 (acid ceramidase) ASAH1 gene. It is characterized by motor neuron disease followed by progressive myoclonic seizures and eventual death due to respiratory insufficiency. Here we report an adolescent female who presented with atonic and absence seizures and myoclonic jerks and was later diagnosed as having myoclonic‐absence seizures. An extensive genetic and metabolic work‐up was unable to arrive at a molecular diagnosis. Whole exome sequencing (WES) identified two rare, deleterious mutations in the ASAH1 gene: c.850G>T;p.Gly284X and c.456A>C;p.Lys152Asn. These mutations were confirmed by Sanger sequencing in the patient and her parents. Functional studies in cultured fibroblasts showed that acid ceramidase was reduced in both overall amount and enzymatic activity. Ceramide level was doubled in the patient's fibroblasts as compared to control cells. The results of the WES and the functional studies prompted an electromyography (EMG) study that showed evidence of motor neuron disease despite only mild proximal muscle weakness. These findings expand the phenotypic spectrum of SMA‐PME caused by novel mutations in ASAH1 and highlight the clinical utility of WES for rare, intractable forms of epilepsy.